2019
DOI: 10.21508/1027-4065-2019-64-3-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal cardiology: the present and the future. Part I: congenital heart disease

Abstract: The article discussesthe currentstate of the care level for fetuses, newborns and children with congenital abnormalities of the cardiovascular system. There are considered the features of prenatal diagnostics of heart defects and aspects of the management of pregnancy and childbirth of women with the specified pathology in the fetus. The authors made the analysis of the existing problems in the diagnosis and treatment of congenital heart defects and heart rhythm disorders in children. The article substantiates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…К настоящему времени в нашей стране отсутствуют клинические рекомендации по ведению беременных женщин с нарушениями ритма сердца и проводимости у плода. В упомянутом в предыдущей части статьи приказе №572н также не определены угрожающие жизни формы нарушений ритма сердца и проводимости у плода, не сформулирована маршрутизация беременных с указанной патологией у плода [9].…”
Section: передоваяunclassified
“…К настоящему времени в нашей стране отсутствуют клинические рекомендации по ведению беременных женщин с нарушениями ритма сердца и проводимости у плода. В упомянутом в предыдущей части статьи приказе №572н также не определены угрожающие жизни формы нарушений ритма сердца и проводимости у плода, не сформулирована маршрутизация беременных с указанной патологией у плода [9].…”
Section: передоваяunclassified
“…When analyzing the gender characteristics of registered CHDs for the period 2018-2020, we noted an increase in the number of male children (p <0.05) (66.4% in 2020 compared to 47.3% in 2018) and a decrease in the number of female children with CHDs (52.7% and 33.6% in 2018 and 2020 respectively). The study of the prevalence of CHD patient groups according to the districts of Osh oblast showed that most often they were registered (2018)(2019)(2020) in Osh, Kara-Suu, and Nookat (26.70%;24.89%;13.58% in 2018., 201927.59%, 24.53%;13.44% in 2018, 201927.56%, 25.45% and 13.65% in 2018, 2019.…”
Section: Resultsmentioning
confidence: 99%
“…According to domestic researchers, it is important to classify CHD according to the criticality of the situation during the neonatal period (ductus-dependent and foramen-dependent) (Manuilenko et al, 2000;Bokeriya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…До 5 тыс. новорожденных детей рождаются с ВПС, при которых хирургическая коррекция необходима в первые сутки жизни [8].…”
Section: современная лучевая диагностика врожденных пороков сердца у ...unclassified